ANALISIS KEBERADAAN UMKM DI BIDANG KULINER DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT KECAMATAN KUALA JAMBI KABUPATEN TANJUNG JABUNG TIMUR - Andri, Wely; Nengsih, Titin Agustin; Sudharyati, Neneng (Lembaga Pengembangan Kinerja Dosen, 2023)
The existence of UMKM greatly contributes to the economy in Indonesia, what's more, the UMKM business in the culinary field never dies.This study aims to determine the impact of the existence of MSMEs in the culinary field on the community's economy and industrial behavior in the culinary field from an Islamic perspective in the Kuala Jambi District Region, East Tanjung Jabung Regency. The type of this research is descriptive qualitative with primary and secondary data types. The data collection technique in this study used observation, interview and documentation techniques. The results of the study explain the impact of UMKM in the culinary field on the community's economy in the Kuala Jambi District, Tanjung Jabung Timur Regency, including the following: there is an increase in the economy because it can create jobs, micro businesses can reduce unemployment because of the impact of UMKM in the culinary field on society and has an impact on increasing people's income even though it is not stable. Industrial behavior carried out in an Islamic perspective in the Kuala Jambi District, East Tanjung Jabung Regency, including culinary business actors, always strives for halal food, service, pricing and financial management as effectively as possible in accordance with Islamic teachings so that the attractiveness of the community continues to increase.